Evaluation of Quality of Life and Care Needs of Turkish Patients Undergoing Hematopoietic Stem Cell Transplantation - Neslisah Yasar; Semiha Akin (Nursing Research and Practice)
This descriptive study explored the quality of life and care needs of Turkish patients who underwent hematopoietic stem cell transplantation. The study sample consisted of 100 hematopoietic stem cell transplant patients. Their quality of life was assessed using Functional Assessment of Cancer Therapy-Bone Marrow Transplant Scale. The mean patient age was 44.99 ± 13.92 years. Changes in sexual functions, loss of hair, loss of taste, loss of appetite, and sleep disturbances were the most common symptoms. The quality of life of transplant patients was moderately affected; the functional well-being and social/family well-being subscales were the most adversely and least negatively affected (12.13 ± 6.88) dimensions, respectively. Being female, being between 50 and 59 years of age, being single, having a chronic disease, and having a history of hospitalization were associated with lower quality of life scores. Interventions to improve functional status, physical well-being, and emotional status of patients during the transplantation process may help patients cope with treatment-related impairments more effectively. Frequent screening and management of patient symptoms in order to help patients adapt to life following allogeneic hematopoietic stem cell transplantation are crucial for meeting care needs and developing strategies to improve their quality of life.